Extra Hepatic Biliary Atresia associated with Choledochal Cyst: A Challenging Neonatal Obstructive Jaundice - Nasrin Fatahi; Ahmad Mohammadipoor; Azin Malekmarzban (EL-Med-Pub, 2014)
Biliary atresia and choledochal cyst have the similar clinical presentation in infants. Herein, we report a case that presented with prolonged hyperbilirubinemia and abdominal distension and diagnosed as choledochal cyst. At surgery, in addition to a large choledochal cyst, biliary atresia was also encountered.